Association Between Water Intake and Mortality Risk—Evidence From a National Prospective Study - Zhou, Hao-long; Wei, Mu-hong; Cui, Yuan; Di, Dong-sheng; Song, Wen-jing; Zhang, Ru-yi; Liu, Jun-an; Wang, Qi (Frontiers in Nutrition, 2022)
Background Few studies have explored the association between water intake and mortality risk, and the findings were inconsistent. Objective This study aimed to explore the water intake–mortality association, utilizing the data from the National Health and Nutrition Examination Survey (NHANES) and the 2015 public-linked mortality files released by the National Center for Health Statistics. Methods We used the diet- and mortality-linked data of a total of 35,463 adults (17,234 men) aged ≥20 years in the NHANESs 1999–2014 to perform a prospective study. The multivariate-adjusted Cox proportional hazards model was used to explore the associations of the amount of water intake (expressed by total water, plain water, beverage, and food water) and water intake proportion (expressed by the percentage of each kind of water) with mortality risks due to all causes, malignant neoplasms/cancer, and heart disease. The restricted cubic spline plots were adopted to clarify the dose–response relationships among them. Results With a median of 88 months (interquartile range: 49–136 months) follow-up, a total of 4,915 all-cause deaths occurred, including 1,073 and 861 deaths from malignant neoplasms/cancer and heart disease, respectively. The amount of water intake in either type was negatively associated with all-cause mortality risk. Additionally, the negative linear dose–response relationships of water intake and all-cause mortality risk were found for all types of water except for food water, which followed a non-linear pattern. Similarly, compared to the lowest quartile (beverage water intake: <676 g/day; food water intake: <532 g/day), beverage and food water intakes in the range of 1,033–1,524 and 1,612–3,802 g/day were associated with decreased malignant neoplasms/cancer mortality risk. A U-shaped dose–response relationship was found for beverage water intake and malignant neoplasms/cancer mortality risk and a negative linear dose–response relationship was found for food water intake and malignant neoplasms/cancer mortality risk. Coffee and/or tea consumption was/were negatively associated with mortality risks due to all causes and malignant neoplasms/cancer. No significant associations of water intake proportion and mortality risks were found. Conclusion Our findings demonstrated that higher water intake is associated with lower mortality risks among the United States population.